Moderate intensity intermittent lifestyle physical activity is associated with better executive function in older adults - Emily MacDonald; Elisabeth G. Morrison; Madeline E. Shivgulam; Liam P. Pellerine; Derek S. Kimmerly; Nick W. Bray; Said Mekari; Said Mekari; Myles W. O’Brien; Myles W. O’Brien (Frontiers in Sports and Active Living, 2024)
Executive functions are among the first cognitive abilities to decline with age and age-related executive function slowing predisposes older adults to cognitive disorders and disease. Intermittent Lifestyle Physical Activity (ILPA) reflects brief, unplanned activity that occurs during routine daily activities and is operationalized as activity bouts <60s. Our understanding of short bouts of habitual physical activity and executive functions is limited. We tested the hypothesis that greater amounts of ILPA in moderate and vigorous intensity domains would be associated with better executive function in older adults. Forty older adults (26 females, 68 ± 6, >55 years; body mass index: 26.6 ± 4.3 kg/m2) completed a Trail-Making-Task and wore an activPAL 24-hr/day for 6.2 ± 1.8-days. For each intensity, total time and time spent in bouts <60 s were determined. Trail A (processing speed) and Trail B (cognitive flexibility) were completed in 25.8 ± 8.2 s and 63.2 ± 26.2 s, respectively. Non-parametric Spearman's rank correlations report that moderate ILPA (3.2 ± 3.2 min/day) and total-moderate physical activity (20.1 ± 16.0 min/day) were associated with faster Trail A (total-moderate physical activity: ρ=−0.48; moderate-ILPA: ρ = −0.50; both, p < 0.003) and Trail B time (total-moderate physical activity: ρ = 0.36; moderate-ILPA: ρ = −0.46; both, p < 0.020). However, the results show no evidence of an association with either vigorous physical activity or light physical activity (total time or ILPA bouts: all, p > 0.180). Moderate physical activity accumulated in longer bouts (>60 s) was not associated with Trail B time (p = 0.201). Therefore, more total moderate physical activity and shorter bouts (<60 s) may result in better executive functions in older adults.